Populus ciliata-a Promising Tree Species for Soil Conservation in Hilly Areas - Mathur, H. N.; Singh, R. P.; Sharma, K. C. (Indian Forester, 1982)
One of the reasons for the important place of Populus ciliata in erosion control is tHat P. ciliata is one of the few species which can be successfully established from branch and stem cuttings. P. ciliata roots easily in shallow soils where other tree species can not be established. Poplars are being used extensively for erosion control and (or the re-vegetation of eroded hilly areas in China, Japan, U.S.A. and New Zealand. P. ciliata has reasonably fast growth rate and strong spreading root system. Plants Grown from cuttings produce and abundance of strong, thick lateral roots with little taper.